The Effect of Electronic Word of Mouth on Brand Attitude and Purchase Intention of Healthy Food Products - Lisnawati, Lisnawati; Setyawan, Anton Agus (Universitas Proklamasi 45, 2024)
The research aims to highlight the effect of e-WOM on brand attitude and purchase intention for healthy food products, particularly on the TikTok platform. The development of digital technology has changed the way consumers receive information and make purchasing decisions, especially among the younger generation. A quantitative research approach was adopted for this study, using surveys as the primary method. The sample consisted of 160 respondents selected through purposive sampling based on specific criteria such as age, occupation, frequently used social media, and preference for healthy food products. The results showed that e-WOM significantly influenced brand attitude and purchase intention. The conclusion highlights the importance of streng-thening e-WOM marketing strategies on TikTok to encourage positive reviews and companies can enhance their brand position in the market. This research is expected to help business practitioners design effective marketing strategies using e-WOM as a promotional medium.